2003
DOI: 10.1002/jbm.b.10070
|View full text |Cite
|
Sign up to set email alerts
|

Ion release and chromosomal damage from total hip prostheses with metal‐on‐metal articulation

Abstract: A prospective multicentric study was carried out in patients having metal-onmetal METASUL components (Sulzer Medica, Winterthur, Switzerland) in order to check the following null hypotheses: H1: The concentration of Co, Cr, Ni, and Mb in blood and urine is not modified by the implant of a hip prosthesis with METASUL components at 6 months. H2: The incidence of markers of chromosomal damage [sister chromatid exchanges (SCEs) and micronuclei (Mni)] in lymphocytes is not modified by the implant of METASUL compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…Our study demonstrated no significant difference in pseudotumor formation in regards to elevated serum cobalt or chromium ion levels. Therefore, it is a possibility that metal ion levels in the blood are only a small representation of the events taking place within the hip itself that leads to pseudotumor formation [21][22][23][24][25]. Consequently, as Macnair et al [26] noted, we feel metal ion levels are not independently sufficient as a screening measure for pseudotumor formation.…”
Section: Accepted Manuscriptmentioning
confidence: 86%
“…Our study demonstrated no significant difference in pseudotumor formation in regards to elevated serum cobalt or chromium ion levels. Therefore, it is a possibility that metal ion levels in the blood are only a small representation of the events taking place within the hip itself that leads to pseudotumor formation [21][22][23][24][25]. Consequently, as Macnair et al [26] noted, we feel metal ion levels are not independently sufficient as a screening measure for pseudotumor formation.…”
Section: Accepted Manuscriptmentioning
confidence: 86%
“…On the other hand, there are experimental proofs as well that cobalt/ chromium do not induce genetic deviations. 21,22 There are also controversial analyses regarding the local effects and induced local toxicity. 23,24 …”
Section: Discussionmentioning
confidence: 99%
“…Urinary excretion of metals provides a possible mechanism for these site-specific cancers (41)(42)(43), although there may not be a relationship between urinary output of metals and markers of chromosomal damage (44).…”
Section: Discussionmentioning
confidence: 99%